1882 Md. Laws 656 ch. 424 §1 - (:unkn) unknown (General Publisher, 1882)
Prohibited the manufacture, sale, barter, or giving away toy pistol cartridges
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES